Education and the requirements of the GCC labour market (Emirates Center for Strategic Studies and Research, 2010)
"To discuss the relationship between education and the labor market in the Arabian Gulf, the Emirates Center for Strategic Studies and Research (ECSSR) convened its 15th Annual Conference under the title Education and the Requirements of the GCC Labor Market on February 1-3, 2010 in Abu Dhabi, UAE, hosting a group of distinguished experts from various academic and professional backgrounds. This book comprises a collection of the papers presented at the conference, and as such provides a scholarly examination of the scale of the current dilemma; methods with which to monitor its indicators - such as population growth rates, the spread of education, foreign labor force concerns, and unemployment; variables of education - labor market dynamics in an international context; and case studies of the relationship between education and the labor market in selected GCC countries, including a review of the various related strategies and policies adopted by these countries - particularly those concerned with labor force nationalization and encouraging greater integration of citizens into the private sector."--Provided by publisher.